Pemberdayaan Pikiran Sadar dan Bawah Sadar dalam Pembelajaran Pendidikan Agama Islam melalui Pendekatan Hypnoteaching: Studi Kualitatif di Kelas VIII MTs - Meifuliardi, Dessi; Mahmud, Salami (Information Technology and Science (ITScience), 2025)
Previous hypnoteaching studies in education predominantly focus on learning outcomes and motivation improvement, while limited attention has been given to the psycho-pedagogical mechanisms of conscious and subconscious mind engagement from students’ lived learning experiences. This gap leaves unanswered questions regarding how hypnoteaching operates internally during classroom interaction, particularly in religious education contexts. This study aims to explore how the conscious and subconscious mind are empowered through hypnoteaching and how students experience light trance conditions in the learning process. Employing a qualitative case study approach, the research was conducted in an Islamic junior secondary school (MTs) involving one teacher and twenty-four eighth-grade students in Pendidikan Agama Islam classes over eight weeks. Data were collected through classroom observations, in-depth interviews, and learning documentation, and analyzed using thematic coding. The findings reveal three major themes: (1) emotional comfort as a gateway to light trance, (2) reduced critical resistance and increased learning receptivity, and (3) internalization of positive belief systems through repetitive suggestion. These findings demonstrate that hypnoteaching functions not merely as a motivational technique but as a humanistic pedagogical mechanism that restructures students’ learning consciousness. This study contributes theoretically by extending hypnoteaching discourse beyond outcome-based evaluation toward experiential and psychopedagogical analysis, and practically by offering an evidence-based framework for reflective hypnoteaching implementation in Islamic education.